2015
DOI: 10.3233/nre-151262
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing function after occipitocervical arthrodesis for cervical deformity in patients with rheumatoid arthritis

Abstract: To the best of our knowledge, this is the first report to evaluate swallowing function before and after O-C3 arthrodesis. The preoperative O-C2 angle was unchanged after surgery. Impairment of deglutition may be closely associated with air leakage from the oropharynx due to impaired mobility of the soft palate. Because the precise mechanism of dysphagia has not been fully elucidated, further study using dynamic videofluoroscopy and videoendoscopy is needed to examine the swallowing mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…On the other hand, C2-C6 angle did not differ significantly between groups. Previous studies in patients who had undergone cervical fusion involving the cranium showed that O-C2 angle was related to the incidence of dysphagia [7][8][9][10][11][12][13][14][15][16]. Since the halo-vest is most effective method of fixation for vertebrae of the upper cervical spine, halo-vest fixation may resemble cervical fusion with the cranium rather than that without the cranium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, C2-C6 angle did not differ significantly between groups. Previous studies in patients who had undergone cervical fusion involving the cranium showed that O-C2 angle was related to the incidence of dysphagia [7][8][9][10][11][12][13][14][15][16]. Since the halo-vest is most effective method of fixation for vertebrae of the upper cervical spine, halo-vest fixation may resemble cervical fusion with the cranium rather than that without the cranium.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who have undergone cervical fusion, accumulating evidence suggests that cervical alignment provides a predictor of postoperative dysphagia [7][8][9][10][11][12][13][14][15][16][17][18]. With occipitocervical fusion, the decrease in O-C2 angle is a predictor of dysphagia after surgery [7][8][9][10][11][12][13][14][15][16]. The decrease in O-C2 angle shifts the mandible posteriorly with the tongue root, resulting in a reduction in the pharyngeal space.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that surgeons should pay more attention to the lower cranial nerve stretch airway obstruction caused by over-distraction of the occiputcervical vertical distance. Shigeto et al reported that the mechanism of dysphagia is not simply associated with the O-C2 angle, but that it also involves global craniocervical alignment in an individual patient, including the occiput-cervical distance [11]. Wang et al reported that performing OCF in the over-distraction position to treat vertical atlantoaxial dislocation may caudally displace the brainstem relative to the cranial base, resulting in traction injury to the 9th, 10th, and 11th lower cranial nerves [12].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that surgeons should pay attention to the lower cranial nerve stretch airway obstruction caused by overdistraction of the occiput-cervical vertical distance. Shigeto E et al reported that the mechanism of dysphagia is not simply associated with the O-C2 angle, but it also involves the global craniocervical alignment in an individual patient, including the occiput-cervical distance [10].Wang Q et al reported that performing OCF in the over-distraction position to treat vertical atlantoaxial dislocation may caudally displace the brainstem relative to the cranial base, resulting in traction injury to the 9 th , 10 th , and 11 th lower cranial nerves [11]. female patients), and the mean neutral OCD was 22.98 ± 5.10 mm (range, 9.88-38.64 mm).…”
Section: Discussionmentioning
confidence: 99%